Adolescent prediabetes in a high-risk Middle East country: a cross-sectional study. (8th July 2014) - Mamtani, Ravinder; Lowenfels, Albert B; Sheikh, Javaid; Cheema, Sohaila; Al-Hamaq, Abdulla; Matthis, Sharoud A; El-Nahas, Katie G; Maisonneuve, Patrick
Objective: To estimate the prevalence of prediabetes in adolescents living in a high-risk country and to detect risk factors associated with this disorder. Design: Survey questionnaire combined with physical measurements and blood sugar determination. Setting: Doha, capital city of Qatar. Participants: A total of 1694 male and female students aged 11–18 years without previously diagnosed diabetes enrolled in four schools. Main outcome measure: Blood sugar measurements. Other measured variables included gender, height, weight, abdominal circumference, country of origin, family history of diabetes and frequency of exercise. Results: Using a random blood sugar ≥7.8 mmol/L or a fasting blood sugar ≥5.5 mmol/L as cutpoints, we identified 4.2% of students (56 boys, 15 girls) as probable prediabetics. In a multivariate model, being boys (OR 3.2, 95% CI 1.7–6.2), having a diabetic parent (OR 1.9, 95% CI 1.1–3.2) or having a waist-to-height ratio >0.5 (OR 1.8, 95% CI 1.1–3.0) were significantly associated with being a prediabetic. The parental origin of diabetes had a differential effect upon blood sugar. The mean random blood sugar in students with a maternal inheritance pattern of diabetes was 5.61 mmol/L ± 1.0, compared to 5.39 mmol/L ± 0.89 in students with a paternal inheritance pattern ( p  = 0.02). Conclusions: In a country with a high risk of adult diabetes, we identified 4.2% of students aged 11–18 as being prediabetic. Risk factors associated with prediabetes included male gender, family history of diabetes and waist-to-height ratio >0.5.